Piecewise damage model for SiC/SiC composites with multilevel experimental validation - Shi, D; Wang, Z; Marrow, J; Liu, C; Wan, F; Yang, X (Elsevier, 2023)
Using multiscale and multidimensional data from experiments and advanced microscopic characterisation, a piecewise damage model for SiC/SiC composite structures has been proposed. First, the geometric information of the microstructure was acquired using scanning electron microscopy (SEM) and X-ray computed tomography (X-CT). High-precision and total-factor finite element models were established, and a piecewise damage model was introduced to simulate in detailing the initiation and propagation of damage. Subsequently, in-situ experiments using the digital image correlation method were conducted to capture the strain fields. After failure, the failure modes were observed and analysed by SEM and X-CT. In the piecewise damage model, observed failure modes were associated within the progressive failure analysis concretely. Combining the multisource data during and after loading, the validity and reliability of this damage model based on failure mechanisms are demonstrated in the accurate prediction of the properties, deformation and stress fields in multilevel structures of SiC/SiC composites.